Percepcja interpersonalna w rodzinach dziewcząt chorych na jadłowstręt psychiczny - Putyński, Leszek (Acta Universitatis Lodziensis. Folia Psychologica, 2013)
The aim of the present study was the analysis of differences in intra and interpersonal perception in families with girls suffering from Anorexia Nervosa and families with healthy controls. Research was conducted among the group of 30 families with AN girl and 30 families with healthy girl. The perception of oneself and family members was investigated with the Semantic Differential Technique constructed by the author of the study. Differences were found in the self-perception and perception of a father between girls with AN and healthy girls (girls with AN have negative self-perception). No significant differences were found in self-perception of mothers and fathers and in perception of their daughters in both family groups.